Management of dynamic curriculum in revitalizing vocational high school graduates - Lispiyatmini Lispiyatmini; Hermanto Hermanto (Jurnal Pendidikan Vokasi, 2022)
This study aims to describe the management of dynamic curriculum implemented by Vocational High School (VHS) Mitra Industri MM2100 in revitalizing its graduates. It was conducted using the qualitative descriptive method at VHS Mitra Industri MM2100 and the object was how VHS Mitra Industri MM2100 implemented a dynamic curriculum. The data were obtained by using a questionnaire, through document studies and observation, and by interviewing principals, deputy principals, heads of departments, and productive teachers. The findings show that VHS Mitra Industri MM2100 implements a dynamic curriculum that always changes according to the development of science, technology, and the needs of graduate users so that the output is in accordance with the expectations and competencies required. The stages of implementing the dynamic curriculum include (1) establishing a learning flow in accordance with the school's vision and mission, (2) involving the industrial sector in curriculum preparation, (3) creating an industrial world ecosystem in the school, (4) adapting the curriculum to changes in the industrial sector and government policies, (5) involving parents in the teaching-learning process maximally, and (6) monitoring and evaluating the implementation of the curriculum on a regular basis by involving all relevant stakeholders. The implementation of a dynamic curriculum at VHS Mitra Industri MM2100 shows the results that match the expectations and competencies needed by the industrial sector, as evidenced by the 100% absorption of graduates for work specialization.